Improvement of Type III Resistant Starch on Food Material Using Hydrotermal Method - Shinta Dewi Ardhiyanti; Bram Kusbiantoro; Adil Basuki Ahza; Didah Nur Faridah (Puslitbang Tanaman Pangan, 2017)
Resistant starch (RS) on food can not be degraded by human digestive enzyme, so that it gives positive effect on human health. The RS content can be enhanced by chemical, enzymatic or physical methods. Physical modification method that is frequently used including heating and cooling cycles, heat moisture treatment/HMT and annealing. These methods generally produce RS type III, which is the product of retrogradation. Physical modification process promotes the reorganization of starch crystalline, which elevate the level of RS or even decrease it. The interaction between intrinsic and extrinsic factors during modification process can produce variation of RS contents in a particular food materials. Different RS analyses method can also induce the variation.